Ethical and aesthetic discourses: a semiotic analysis of photo editorials of fast fashion and slow fashion brands (ModaPalavra e-periódico, 2021)
In this article, the symbolic values and discursive strategies present in fashion editorials produced by two different models of clothing companies are analyzed: one fast fashion brand and one slow fashion brand. To this end, the theoretical-methodological apparatus of discursive semiotics developed by Algirdas Julien Greimas is used, with a view to raising interpretive hypotheses and apprehending the effects of meaning linked to the photographic images of these two business models. As a result, the readings of the visual elements that are part of the analyzed editorials suggest the promotion of distinct values that point to the possible ideological positions discursivized by the brands.
Keywords: fashion; sustainability; discursive semiotics